An integrative approach unveils speciation within the threatened spider Calathotarsus simoni (Araneae: Mygalomorphae: Migidae). Issue 5 (4th July 2019) - Ferretti, Nelson E.; Soresi, Daniela S.; González, Alda; Arnedo, Miquel
Abstract : The mygalomorph trapdoor spider family Migidae displays a quintessential Gondwanan distribution, including species in Australia, Africa, Madagascar, New Zealand, New Caledonia, and the southern cone of South America. The Argentinean fauna consists of a single species, Calathotarsus simoni Schiapelli & Gerschman, 1975, with a highly localized distribution range restricted to two mountain ranges in the southern Buenos Aires province, central Argentina. The recent discovery of specimens from new localities including adult males and females revealed morphological differences. Similarly, a molecular phylogenetic analysis using mitochondrial and nuclear markers distinguished two main lineages within C. simoni, showing genetic divergence in the levels reported for other species within the family. The two lineages corresponded to each of the two main ranges inhabited by the species and matched the morphological differences observed. Finally, an ecological niche modelling analysis revealed significant ecological differences between the lineages inhabiting the two mountain ranges. Based on integration of all the evidence, the new species Calathotarsus fangioi sp. nov. is described. The new species is circumscribed to the easternmost mountain range of Tandilia, while the distribution C. simoni is re-delimited to include only the western range of Ventania. Both species are diagnosed, described, and illustrated. This new species description and the conservation status for these remarkable spiders are further discussed.